From ‘on’ to ‘with’ to ‘by:’ people with a learning disability creating a space for the third wave of Inclusive Research - Milner, Paul; Frawley, Patsie (Qualitative research : QR, 2019)
For people with a learning disability, Inclusive Research is promoted as the right way to redress the hermeneutical injustice of their voices and theorising being excluded from the processes of knowledge production. This article describes the experiences and reflections of non-disabled researchers co-researching with people whose subjectivities were thought to lie beyond qualitative research. Through four stories, jointly told, we detail how those most at risk of exclusion from the academy first challenged and then took the research encounter beyond the linear, assimilative certainties of research ‘on’ or ‘with’ people with a learning disability towards the outer, cutting edges of qualitative research and an epistemology that might more authentically be said to be ‘by’ them.